FORMING THE CHARACTER OF STUDENTS IN MA ISLAMIC SYAFI'IYAH PAITON THROUGH ISLAM-BASED EDUCATION MANAGEMENT - Dewi, Dianita Santia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze the character formation of students at MA Islamiyah Syafi'iyah Paiton through Islamic-based education management. The research method used is a qualitative method in which researchers work directly in the field to make detailed, detailed and in-depth direct observations. The research location is at MA Islamiyah Syafi'iyah Paiton Probolinggo. In this study, the researchers involved the Principal, Deputy Head of Curriculum, Deputy Student Affairs and Deputy Deputy for Religious Affairs by carrying out data collection techniques through three stages, namely: participant observation, in-depth interviews and documentation studies. The data that has been collected is analyzed using an interactive model with the flow of data recording, data reduction, data presentation and conclusions. The results of the study show that the formation of students' character through Islamic-based education management where the functions of Islamic education management which include planning, organizing, directing, and supervising are indispensable in student character education. Documentally, student character education can be integrated into the institutional curriculum. The character values of students can be integrated into lesson plans or what is now commonly called teaching modules because they already use an independent curriculum.